Effects of histamine on human periodontal ligament fibroblasts under simulated orthodontic pressure - Groeger, Marcella (PLoS One, 2020)
As type-I-allergies show an increasing prevalence in the general populace, orthodontic patients may also be affected by histamine release during treatment. Human periodontal ligament fibroblasts (PDLF) are regulators of orthodontic tooth movement. However, the impact of histamine on PDLF in this regard is unknown. Therefore PDLF were incubated without or with an orthodontic compressive force of 2g/cm(2) with and without additional histamine. To assess the role of histamine-1-receptor (H1R) H1R-antagonist cetirizine was used. Expression of histamine receptors and important mediators of orthodontic tooth movement were investigated. PDLF expressed histamine receptors H1R, H2R and H4R, but not H3R. Histamine increased the expression of H1R, H2R and H4R as well as of interleukin-6, cyclooxygenase-2, and prostaglandin-E2 secretion even without pressure application and induced receptor activator of NF-kB ligand (RANKL) protein expression with unchanged osteoprotegerin secretion. These effects were not observed in presence of H1R antagonist cetirizine. By expressing histamine receptors, PDLF seem to be able to respond to fluctuating histamine levels in the periodontal tissue. Increased histamine concentration was associated with enhanced expression of proinflammatory mediators and RANKL, suggesting an inductive effect of histamine on PDLF-mediated osteoclastogenesis and orthodontic tooth movement. Since cetirizine inhibited these effects, they seem to be mainly mediated via histamine receptor H1R.